SMARTPHONE BASEDFACE AND VOICE AUTHENTICATION IN MOBILE DEVICESBY USING MFCC ALGORITHM (International Journal of Engineering Sciences & Management Research, 2015)
The Smart phones are capable of doing new kind of protection mechanism for sensitive data stored in the mobile. Smartphones with camera and microphone can be used for biometric authentication mechanism to protect data which is stored in the phone memory. All human voice is unique in nature. Using the integrated camera on the mobile device we can verify that users are who they claim to be from their facial biometrics. This work based on making rapid authentication using face variations and voice biometrics.